Religious Fatwā and Human Security: Managing Public Health through the Lens of Islamic Jurisprudence in Indonesia and Saudi Arabia - Khairul Hamim; Lalu Supriadi Bin Mujib; Ahmad Muhasim (Khazanah Hukum)
This study examines the authorisation of religion in handling COVID-19 through religious fatwā issued by the Indonesian Ulema Council, popularly known as the Majelis Ulama’ Indonesia (MUI), and the Council of Senior Scholars of Saudi Arabia (CSS). The objectives of this study are threefold: firstly, to analyse the methodological formulation of MUI and CSS fatwā regarding COVID-19 handling; secondly, to identify the factors underlying the issuance of these fatwā; and thirdly, to assess the impact of MUI and CSS fatwā on COVID-19 handling. Using a qualitative descriptive research method and conducting a case study of the MUI and CSS fatwā institutions, it was found that the methodological basis of the MUI and CSS fatwā on COVID-19 includes sources from the Qur’an, hadith, ijmā’ (consensus), and qiyas (analogy), as well as maqāṣīd sharī’ah. Referring to maqāṣīd sharī’ah considerations, two priority dimensions emerge as factors in the issuance of MUI and CSS fatwā: ḥifẓ al-dīn (preservation of religion) and ḥifẓ al-nafs (preservation of life). This study also highlights the significant impact of MUI and CSS fatwā on COVID-19 handling. In this context, fatwā play a role as part of prevention strategies due to their strong theological influence and effective enforcement of policy implementation. This fatwā is especially pertinent given the roles of MUI and CSS, which, from the early stages of the COVID-19 pandemic, have contributed to supporting government policies through the fatwā they issued. However, differences exist. MUI fatwā tend to be recommendations and appeals, often disregarded by the public as they lack legal sanctions for non-compliance. However, fatwā issued by CSS possess absolute authority. This study contributes to a deeper understanding of how religious authorization can support public health policies during a pandemic. Additionally, it offers insights for enhancing the effectiveness of fatwā in the context of future health crises.